Corrigendum to "New insights to understand the influence of hairy vetch on maize yield and its response to nitrogen application" [Eur. J. Agron. 162 (2025) 127434] (European Journal of Agronomy (2025) 162, (S1161030124003551), (10.1016/j.eja.2024.127434)). [Erratum] - CAFARO LA MENZA, F. (2025)
ABSTRACT.- Refers to original document: "New insights to understand the influence of hairy vetch on maize yield and its response to nitrogen application", European Journal of Agronomy, Volume 162, January 2025, Pages 127434. Francisco Cafaro La Menza, Fernando Salvagiotti, Nicolas E. Maltese, Roxana P. Eclesia, Mirian Barraco, Laura Echarte, Pablo A. Barbieri, Walter D. Carciochi. ---- The authors regret a misspelling in the abstract. Instead of stating, "We conducted 70 experiments evaluating four treatments resulting from the inclusion (or not) of hairy vetch previous to maize with and without subsequent N fertilization," it should read, "Seventy experiments were conducted to evaluate four treatments resulting from the inclusion (or not) of hairy vetch prior to maize, with and without subsequent N fertilization.? In addition, a column indicating the source of each experiment was missing in Supplementary Table 1. The updated Supplementary Table 1 is as follows: The authors would like to apologise for any inconvenience caused. Appendix A. Supporting information Supplementary data associated with this article can be found in the online version at doi:10.1016/j.eja.2025.127583. Appendix A. Supplementary material © 2025 Elsevier B.V.